2023
DOI: 10.1002/cne.25463
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fragile X Mental Retardation Protein expression in human nociceptors and their axonal projections to the spinal dorsal horn

Abstract: Fragile X Mental Retardation Protein (FMRP) regulates activity‐dependent RNA localization and local translation to modulate synaptic plasticity throughout the central nervous system. Mutations in the FMR1 gene that hinder or ablate FMRP function cause Fragile X Syndrome (FXS), a disorder associated with sensory processing dysfunction. FXS premutations are associated with increased FMRP expression and neurological impairments including sex dimorphic presentations of chronic pain. In mice, FMRP ablation causes d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 185 publications
(388 reference statements)
0
4
0
Order By: Relevance
“…Click chemistry reactions were carried out at room temperature while mixing for 20 to 24 hrs. Sections were then processed for immunofluorescence (IF) to detect either TRPV1 (488) or p-S209-eIF4E (488 or 555) and NeuN (488 or 555) (Shiers et al, 2021; Mitchell et al, 2023). All antibodies used in this study are listed in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Click chemistry reactions were carried out at room temperature while mixing for 20 to 24 hrs. Sections were then processed for immunofluorescence (IF) to detect either TRPV1 (488) or p-S209-eIF4E (488 or 555) and NeuN (488 or 555) (Shiers et al, 2021; Mitchell et al, 2023). All antibodies used in this study are listed in Table 3 .…”
Section: Methodsmentioning
confidence: 99%
“…For DRG neuronal somata, ROIs were identified in 12-bit images of TRPV1 IF (nociceptors) or NeuN IF (DRG neurons) channels. Somata were defined as having a minimum surface area of 350 µm 2 (Mitchell et al, 2023)1. Then, raw FUNCAT and/or p-eIF4E IF signals were measured per ROI, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other manifestations of CN VIII toxicity in FXTAS include hearing loss, tinnitus, and imbalance, which are common [15,27,37]. A study by Mitchell et al [38] revealed that FMRP may be a modulator of calcitonin gene-related peptide (CGRP) signaling in nociceptive sensitization and chronic pain. CGRP signaling plays an important role in hearing and balance and the development of migraine [39]; therefore, altered levels of FMRP in premutation carriers could contribute to further dysfunction of CN VIII and increased risk of developing VM.…”
Section: Vm and Fxtasmentioning
confidence: 99%